Mentorship/portfolio program in early medical years, is it the perfect twinning? : mentoring portfolio twinning program - Abouzeid, Enjy; Wasfy, Nourhan; Alkhadragy, Rania (Advances in Social Sciences Research Journal, 2021)
Objectives: Compiling the portfolio in the early years of medical study is considered an important educational instrument for fostering change in the medical education curriculum in Egypt. This study assumed that adding the mentorship may boost the effectiveness of this program. This study was conducted at the Faculty of Medicine, Suez Canal University in early years of medical study with the following objectives: assessing the effects of mentoring portfolios on students and staff, exploring how mentors and students perceived the mentorship/ portfolio program, and determining any suggestions to improve the program Methodology: This is a cross-sectional study, sample included a total comprehensive sample of year 1 students (n=260 students) and Seventeen mentors. Two questionnaires were used: Students' perception questionnaire and Mentors' perception questionnaire. Results: Mentorship has helped in the implementation of the portfolio as all mentors agreed that mentorship improved the final product of the portfolio and facilitated the process of the portfolio. The twining has supported the students academically and professionally. Academically as students agreed that their mentors assist in portfolio understanding, 68.3%, provide constructive feedback 67.4%, and follow the fulfilment of all the portfolio inputs 65.6%. It helped them to develop personally and professionally through the development of their reflective skills, 59.6% and the concept map 64%. Conclusion: The study concluded that the mentorship may help improvement of the final product of the portfolio in the early basic years. Moreover, it assists the academic support to the students and helps them to develop their reflective skills.